An Empirical Approach in Culinary Fiqh of Coastal Communities: Critical Study of ‘Aysh al-Baḥr - Zainul Mun'im; Abdussamet Kaya (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
The lives of fishermen are said to have a profound influence on the lives of coastal towns. Their attitude toward marine resources effects their theological perspective as well. This fact is supported by Kiai Anwar's book ‘Aysh al-Baḥr, which discusses the legal position of consuming numerous aquatic animals. This article seeks to trace the book ‘Aysh al-Baḥr's understanding of culinary fiqh. As an analytical tool, this paper employs a normative approach and the notion of Islamic epistemology pioneered by al-Jābirī and Mulyadhi. This article demonstrates how the epistemology of culinary fiqh in ‘Aysh al-Baḥr employs an empirical approach to determining the legal status of ingesting animals by viewing and direct observing them. Kiai Anwar's background as a fisherman gives him an edge in developing normative and empirical reasons for marine animal laws. This conclusion demonstrates that coastal cultures have an extensive understanding of aquatic animal environments. This article suggests utilizing empirical approaches to derive rules that necessitate direct observation.__________The original draft of this article has been presented at the 20th Annual International Conference on Islamic Studies (AICIS), Surakarta, 2021.